2020
DOI: 10.1515/bot-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of macroalgal traits on the feeding behaviour of a generalist herbivore in Malaysian waters

Abstract: With the potential adverse effects of climate change, it is essential to enhance the understanding of marine ecosystem dynamics, which can be driven by the co-evolutionary interaction between autotrophs and herbivores. This study looked into the autotroph-herbivore interactions in Malaysian waters, mainly to determine if autotroph nutritional quality significantly influences herbivore consumption rates. We documented the relative consumption rate of a generalist herbivore (Chanos chanos Forsskål) obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Living organisms require nitrogen to synthesize amino acids, the basic building blocks of protein that serve essential functions in virtually all biological processes [ 153 ]. Many previous studies have pointed out that low nitrogen consumption is associated with reduced food intake in generalist marine herbivores [ 39 , 148 , 160 , 161 , 162 , 163 ]. The study by Barile, Lapointe and Capo [ 156 ] on California sea hare ( Aplysia californica ) showed that this herbivorous gastropod preferred to feed on gracilarioid algae ( Gracilaria ferox ) with high levels of nitrogen.…”
Section: Does Nutrient Acquisition In Algae Determine the Feeding Pre...mentioning
confidence: 99%
See 2 more Smart Citations
“…Living organisms require nitrogen to synthesize amino acids, the basic building blocks of protein that serve essential functions in virtually all biological processes [ 153 ]. Many previous studies have pointed out that low nitrogen consumption is associated with reduced food intake in generalist marine herbivores [ 39 , 148 , 160 , 161 , 162 , 163 ]. The study by Barile, Lapointe and Capo [ 156 ] on California sea hare ( Aplysia californica ) showed that this herbivorous gastropod preferred to feed on gracilarioid algae ( Gracilaria ferox ) with high levels of nitrogen.…”
Section: Does Nutrient Acquisition In Algae Determine the Feeding Pre...mentioning
confidence: 99%
“…The lack of preference for protein-enriched algae (i.e., high-nutrient algae) can be explained by the compensatory feeding behaviour of some herbivore species. Previous studies reported the optimal growth rate and adequate intakes of limiting nutrients by testing the consumption rates of different herbivores on the low nutritional quality of algae foods [ 39 , 43 , 164 , 165 ]. According to Bradley et al (2021), herbivores may avoid species that are less palatable or have lower nutritional value, which may affect their distribution and abundance [ 164 ].…”
Section: Does Nutrient Acquisition In Algae Determine the Feeding Pre...mentioning
confidence: 99%
See 1 more Smart Citation